Pharmacological validation of an attention bias test for conventional broiler chickens - da Silva, Marconi Italo Lourenço [UNESP]; Ulans, Alexandra; Jacobs, Leonie (Public Library of Science (PLoS), 2024)
Fear and anxiety are considered concerns for animal welfare as they are associated with negative affective states. This study aimed to pharmacologically validate an attention bias test (ABT) for broiler chickens (Gallus gallus domesticus) as a cognitive bias test to determine anxiety. Two-hundred-and-four male Ross 708 broiler chickens were arbitrarily allocated to either the anxiogenic or control treatment at 25 days of age (n = 102/treatment). Birds from the anxiogenic group were administered with 2.5 mg of β-CCM (β-carboline-3-carboxylic acid-N-methylamide [FG 7142]) per kg of body weight through an intraperitoneal injection (0.1 ml/100 g of body weight). Birds from the control group were administered with 9 mg of a saline solution per kg of body weight. During ABT, birds were tested in groups of three (n = 34 groups of three birds/treatment) with commercial feed and mealworms as positive stimuli and a conspecific alarm call as a negative stimulus. Control birds were 45 s faster to begin feeding than anxiogenic birds. Birds from the control group vocalized 40 s later and stepped 57 s later than birds from the anxiogenic group. The occurrence of vigilance behaviors did not differ between treatments. This study was successful in pharmacologically validating an attention bias test for fast-growing broiler chickens, testing three birds simultaneously. Our findings showed that latencies to begin feeding, first vocalization, and first step were valid measures to quantify anxiety.